Analisis Pengendalian Internal Pelaporan Keuangan Guna Peningkatan Kualitas Laporan Keuangan dalam Rangka Mendukung Tugas Staf Kebijakan dan Perencanaan Umum TNI - Aditya Yuda Negara; Elisabeth Tanti; Mohamad Rachmad (EduInovasi: Journal of Basic Educational Studies, 2026)
The implementation of Internal Control over Financial Reporting (ICFR/PIPK) is a vital foundation for Srenum TNI (General Policy and Planning Staff of the Indonesian National Armed Forces) to produce accurate financial information as a basis for strategic decision-making by the TNI Commander. This study aims to analyze the effectiveness of PIPK implementation at the Srenum TNI unit and identify the challenges faced in improving the quality of financial statements in accordance with government accounting standards. The research methodology employs a descriptive qualitative approach with a Control Self-Assessment (CSA) framework, as mandated by Minister of Finance Regulation (PMK) No. 17/2019. Data collection was conducted through technical triangulation, including: (1) Document Review of the five components of internal control; (2) Technical Interviews with treasury officials and SAKTI application operators; and (3) a Quantitative Survey involving 87 Srenum TNI personnel to measure perceptions of the control environment. The analysis focused on significant accounts—such as equipment, machinery, and inventory—through reperformance procedures within the SAKTI and SIMAK BMN applications. The results indicate that Srenum TNI has achieved "Effective Internal Control" (PIE) status. This effectiveness is attributed to the integration of risk management into organizational SOPs and the optimization of Information Technology and Manual (ITDM) monitoring systems. However, the optimization of PIPK is still hindered by three primary constraints: limited personnel quantity leading to a double burden of tasks, a technical skill gap regarding complex digital system features, and high personnel rotation (tour of duty), which disrupts the continuity of knowledge management. The study recommends strengthening institutionalized knowledge management and continuous technical certification to maintain the integrity of financial reporting in support of TNI’s bureaucratic transformation.